2020
DOI: 10.1021/acschemneuro.0c00014
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Cocaine, Drug Removal, and Methylphenidate Reversal on Phospholipid Alterations in Drosophila Brain Determined by Imaging Mass Spectrometry

Abstract: Cocaine dependence displays a broad impairment in cognitive performance including attention, learning, and memory. To obtain a better understanding of the action of cocaine in the nervous system, and the relation between phospholipids and memory, we have investigated whether phospholipids recover in the brain following cocaine removal using the fly model, Drosophila melanogaster. In addition, the effects of methylphenidate, a substitute medication for cocaine dependence, on fly brain lipids after cocaine abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Thus, ToF-SIMS has become an important tool in multiple research areas, especially in the biological field [ 15 , 16 ]. This technique has been applied to analyze changes of lipid species in cells and tissues caused by drug treatments, diseases, or injuries [ 17 , 18 , 19 , 20 , 21 ]. Furthermore, the connection between lipid changes and the alteration of exocytotic release induced by chemical effectors or drugs has been investigated by multiple studies in PC12 cells using ToF-SIMS [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ToF-SIMS has become an important tool in multiple research areas, especially in the biological field [ 15 , 16 ]. This technique has been applied to analyze changes of lipid species in cells and tissues caused by drug treatments, diseases, or injuries [ 17 , 18 , 19 , 20 , 21 ]. Furthermore, the connection between lipid changes and the alteration of exocytotic release induced by chemical effectors or drugs has been investigated by multiple studies in PC12 cells using ToF-SIMS [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that cocaine increased the level of phosphatidylcholines and decreased the levels of phosphatidylethanolamines and phosphatidylinositols. Methylphenidate-treated flies failed to rescue the levels of phosphatidylethanolamines and phosphatidylinositols, but enhanced the reversal of phosphatidylcholine levels [49].…”
Section: Drug/pharmacological Testmentioning
confidence: 90%
“…For example, glycerophospholipids, phosphatidylcholines, and phosphatidylethanolamines are basic components of cell and lysophospholipids have an important function in inflammation, abiotic stress, and biotic stress signal transmit [42]. MSI has been widely applied in many aspects in model insect Drosophila melanogaster, such as the neutral lipids three-dimensional spatial distribution on the surface adults [43,44], body lipid distribution [45], brain lipid structure [46,47], wing lipids [34,44], Malpighian tubule phospholipid distribution [48], and phospholipids in the brain treated with cocaine [49]. Moreover, MSI detected and localized the composition and distribution of triacylglyceride in Aedes aegypti, phospholipid and phosphatidylcholine in Anopheles stephensi [42], and phospholipids in Schistocerca gregaria [37].…”
Section: Lipidsmentioning
confidence: 99%
“…The TOF-SIMS analysis was done using a J105-3D Chemical Imager (Ionoptika Ltd., UK) equipped with a GCIB of 40 keV (CO 2 ) 6000 + ion beam to sputter 1,000 × 1,000 μm 2 in positive and negative modes. The results show that methylphenidate treatment does not reverse the alterations of cocaine addiction, but rather establishes a positive effect in reducing the lipids levels to the original control level (Philipsen et al, 2020). In the same year, Yarixa et al studied the assessment of ABT-737, potential cancer chemotherapy, using a TOF-SIMS instrument from ION-TOF, Münster, Germany equipped with an LMIG (25 keV, Bi 3 + ).…”
Section: Drug Detection: Pharmacologymentioning
confidence: 99%